2017
DOI: 10.1038/pr.2017.218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics on experimental necrotizing enterocolitis: a systematic review and meta-analysis

Abstract: BackgroundMeta-analyses of randomized controlled trials (RCTs) suggest that probiotics decrease the risk of necrotizing enterocolitis (NEC) in preterm infants. Many animal RCTs have evaluated probiotics for preventing NEC. We systematically reviewed the literature on this topic.MethodsThe protocol for systematic review of animal intervention studies (SYRCLE) was followed. Medline, Embase, ISI Web of Science, e-abstracts from the Pediatric Academic Society meetings, and other neonatal conferences were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 91 publications
2
33
0
Order By: Relevance
“…For this reason, meta-analyses will often contain a funnel plot, an asymmetry of which is a way of determining publication bias [ 126 ]. Funnel plots for probiotic studies have generally shown no publication bias for probiotics in most of the conditions described, such as NEC prevention [ 127 ], IBS improvement [ 128 ], H. pylori eradication [ 129 ], and amelioration of infant colic [ 130 ]. Nevertheless, there is much work to do in identifying optimal strains and using meta-analysis to prove the effect size of the disease (which in some cases may be significant, but only minor).…”
Section: “Polarization” Within the Medical Community Regarding Thementioning
confidence: 99%
“…For this reason, meta-analyses will often contain a funnel plot, an asymmetry of which is a way of determining publication bias [ 126 ]. Funnel plots for probiotic studies have generally shown no publication bias for probiotics in most of the conditions described, such as NEC prevention [ 127 ], IBS improvement [ 128 ], H. pylori eradication [ 129 ], and amelioration of infant colic [ 130 ]. Nevertheless, there is much work to do in identifying optimal strains and using meta-analysis to prove the effect size of the disease (which in some cases may be significant, but only minor).…”
Section: “Polarization” Within the Medical Community Regarding Thementioning
confidence: 99%
“…Studies specifically with Lactobacillus GG administered as a treatment modality, during acute rotavirus infections with diarrhea has been reported and associated with higher titres of polymeric immunoglobulin A to the infections with rotavirus ( 119 , 120 ). Additionally, significant experimental and clinical studies have reported the efficacy for reducing the incidence of neonatal necrotizing enterocolitis with the administration of Lactobalcilli and Bifidobacteria ( 121 , 122 ). Increased efficacy of probiotics have recently been reported to significantly decrease the risk of developing clinical complications related with necrotizing enterocolitis and sepsis; decrease mortality and length of hospital stay; as well as promote neonatal weight increases in very low birth weight infants ( 123 ).…”
Section: Probioticsmentioning
confidence: 99%
“…eczema but not in rheumatoid arthritis. [16][17][18][19][20] There has also been a clinical trial reporting that administration of Bifidobacterium mixture may attenuate dry eye syndrome. 21 IRT5 is a probiotic mixture of five strains that includes Bifidobacterium bifidum, Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus reuteri, and Streptococcus thermophilus.…”
mentioning
confidence: 99%